Entrepreneurial Ability Analysis At Sumedang Crispy Tofu Restaurant In Pangkep Regency - Firdaus, Hamda Putri; Haris, Hasnawi; Saleh, Sirajuddin (Jurnal Administrasi Bisnis, 2025)
Analysis of Entrepreneurial Ability at Crispy Sumedang Tofu Restaurant in Pangkep Regency. Thesis. Business Administration Study Program. Administration Science Department. Faculty of Social Sciences and Law. Makassar public university. Supervised by Hasnawi Haris and Sirajuddin Saleh. This study aims to determine the impact of entrepreneurship skills on Crispy Sumedang Tofu Restaurant in Pangkep Regency. This study used qualitative research methods. Data collection techniques carried out are through observation, interviews, and documentation. The number of informants in this study is five people who are representative and meet the criteria in this study. Data analysis techniques in this study used data collection, data presentation, and drawing conclusions. The results of this study indicate that the impact of the entrepreneurial ability of Crispy Sumedang Tofu in Pangkep Regency is based on indicators of initiative and proactivity, namely that business actors have succeeded in increasing operational efficiency and have played an important role in finding innovative solutions to be able to face the challenges of the business world. Courage to face risks, by mitigating risks in order to survive in the midst of a situation that cannot be denied. Achievement oriented by taking advantage of business opportunities, developing effective strategies, and upholding professionalism in work, as well as commitments with various parties, namely customers, employees, partners, for mutual benefit.